Does halal logo influence Muslim purchase decision? A comparative study between extrinsic and intrinsic religious people / Waida Irani Mohd Fauzi...[et al.] - Mohd Fauzi, Waida Irani; Khamarudin, Munirah; Mohd Mokhtar, Sany Sanuri; Yusr, Maha (Universiti Teknologi MARA, Kedah, 2019)
Recently , halal issues have been brought to the attention of Malay Muslim consumers. Some of them trust halal logo and some of them do not. Consumer action in purchasing a product is depends on their school of thought and the role of religiosity. Extrinsic religious people mostly trust halal logo in their purchasing behavior, however, intrinsic religious people have their own judgment and additional criteria in purchasing a product. There is a higher halal consciousness among them, when a halal logo is not become a primary indicator to determine halal status. Thus, this paper tries to investigate the significant relationship of halal logo towards extrinsic as compared to intrinsic religious people in their purchasing decision. The study use mall intercepts approach to distribute a questionnaires. Result of the study reveals that, the extrinsic religious people have strong trust towards halal logo as compared to intrinsic people. Intrinsic religious people do not rely on halal logo itself but they put more trust on the owner of thestore and they are more concern on the ingredients of the product and usually prefer muslim made product. The finding of this study may have an implication towards JAKIM who are trusted body in issuing halal logo.